2017
DOI: 10.5603/arm.2017.0004
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Health Education Given by Nurses to COPD Patients on the Daily Oxygen Concentrator Usage Time

Abstract: Introduction: Long-term oxygen therapy is the most effective method which has been shown to prolong the lifespan in people with COPD. The aim of the study was to investigate the effects of health education given by nurses to patients with COPD on the daily oxygen concentrator (OC) usage time. Material and methods:The study was carried out in a State Hospital, Turkey, between July and November 2015. After given consent to the study, participants were divided into intervention and control groups by simple random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 7 publications
(7 reference statements)
0
10
0
Order By: Relevance
“…Specifically, twenty studies [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ] reported data on hospital nurse management with a specific care plan of pharmacological management to empower COPD patients, i.e., correctly performed inhalation therapy training, use of oxygen therapy, and physical exercise, which are typically given on post-discharge home visits.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, twenty studies [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ] reported data on hospital nurse management with a specific care plan of pharmacological management to empower COPD patients, i.e., correctly performed inhalation therapy training, use of oxygen therapy, and physical exercise, which are typically given on post-discharge home visits.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies [ 50 , 51 ] analyzed the collaboration between primary care nurses and hospital nurses at discharge time and the follow-up of COPD patients in the management of COPD disease, and four studies [ 15 , 16 , 52 , 53 ] analyzed inhalation drug training techniques given by specialized nurses with COPD patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Collinsworth et al19 reported that the time to first all-cause and COPD-related readmission appeared shorter for patients receiving education. Dogan and Ovayolu et al20 found that the health education provided by nurses to COPD patients can significantly improve PaO 2 , PaCO 2 , FEV 1 and SaO 2 of patients in the education group. Nurses and physicians are primarily responsible for education and this has also been proved in patients’ perspective 7.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we found that extended care elevated the level of PaO 2 and reduced the level of PaCO 2 in COPD patients compared with usual care, suggesting that extended care not only can alleviate the physical and mental burden of patients but also directly improve blood gas levels of COPD patients. Previous study shows that the extended care is beneficial to ensure the patient compliance to lung function rehabilitation training, family oxygen therapy, drug therapy and breathing training, thus promoting the arterial oxygen pressure levels and decreasing the levels of PaCO 2 23…”
Section: Discussionmentioning
confidence: 99%